The effects on tuberculosis treatment adherence from utilising community health workers: a comparison of selected rural and urban settings in Kenya. - Jane Rahedi Ong'ang'o; Christina Mwachari; Hillary Kipruto; Simon Karanja (PLoS ONE)
Introduction Community Health Workers (CHWs) have been utilised for various primary health care activities in different settings especially in developing countries. Usually when utilised in well defined terms, they have a positive impact. To support Kenya's policy on engagement of CHWs for tuberculosis (TB) control, there is need to demonstrate effects of utilising them. Objectives This study assessed TB treatment adherence among patients who utilised CHWs in management of their illness in comparison to those who did not in urban and rural settings. Methods A retrospective cohort study was conducted in selected health facilities using standard clinical records for each TB patient registered for treatment between 2005 to 2011. Qualitative data was collected from CHWs and health care providers. Results The study assessed 2778 tuberculosis patients and among them 1499 (54%) utilized CHWs for their TB treatment. The urban setting in comparison with the rural setting contributed 70% of patients utilising the CHWs (p<0.001). Overall treatment adherence of the cohort was 79%. Categorizing by use of CHWs, adherence among patients who had utilized CHWs was 83% versus 68% among those that had not (p<0.001). In comparison between the rural and urban settings adherence was 76% and 81.5% (p<0.001) respectively and when categorized by use of CHWs it was 73% and 90% (p<0.001) for the rural and urban set ups respectively. Utilisation of CHWs remained significant in enhancing treatment adherence in the cohort with unadjusted and adjusted ORs; OR 2.25, (95% 1.86-2.73) p<0.001 and OR 1.98 (95% 1.51-2.5) p<0.001 respectively. It was most effective in the urban set-up, OR 2.65 (95% 2.02-3.48, p<0.001) in comparison to the rural set up, OR 0.74 (95% 0.56-0.97) p = 0.032. Conclusion Utilisation of CHWs enhanced TB treatment adherence and the best effects were in the urban set-up.